Innovación y desarrollo de nuevos productos. Caso Alaska Mousse D’Onofrio - Ramón Musaurieta, Sonia Hermelinda (2021)
Innovation is any change that generates value for the consumer and for society, which is why it is considered a pillar of growth in the ice cream industry, such is the case of D’Onofrio’s Alaska Mousse. The objective of the article is to understand the relevant attributes of the fruit ice cream category through the attitudes and behavior of the consumer of the brand, who is becoming increasingly rational and selective when planning their spending; for this purpose the exploratory qualitative methodology has been used through four Focus Groups, The reactions to the test were very positive, so we have that the relevant attributes for the mentioned target in the first place is the naturalness, secondly, the taste, especially that it is close to the real taste of the fruit, without perception of intense or artificial flavorings and with a balanced sweetness level mainly. It should be noted that since the application of the product innovation strategy and following the new product development process, sales have increased, even in the winter season.